Roblib: A library of models for industrial robots - Cordeiro, Carla S. M. (2019)
This paper describes a software package developed in the Windows environment. This software consists of a library for industrial robots models and allows the calculation of the direct and the inverse kinematics for several manipulators. The program allows trajectory planning algorithms, both in the joint and cartesian spaces, using linear or cubic splines interpolation procedures. The kinematic equatinos for each robot were optimised in what concerns the number of required operatinos in order to optimize the computational load.